Characterization of the translational shear properties of the magnetorheological elastomers embedding the tilt chain-like structure - Lin Dezhao; Gong Di; Yang Fan; Li Ruihong; Zhang Weiqiang (Applied Rheology)
In this study, the translational shear characteristics of the magnetorheological elastomers (MREs) with different chain-like structure angles (0°–90° with 15° increment) are tested and analyzed in detail. The experiments are performed under board ranges of strain amplitudes (1–20%), excitation frequencies (0.1–50 Hz), and magnetic fields (0–375 mT). The measured force-displacement data are utilized to analyze the role of chain-like structure angles on the viscoelastic properties together with their dependency on the excitation conditions, mass ratio of magnetic particles, and the magnetic field. The results illustrate that compared with the isotropic MREs and anisotropic MREs with symmetrical chain-like structures, the anisotropic MREs with the tilt chain-like structure can provide more significant variations in the average storage and loss moduli with a slight effect on the zero-field viscoelastic properties, and it exhibits higher frequency and strain dependencies. It can also suggest that the MREs with 30° chain-like structure have the largest MR effect. Besides, the mass ratio of the magnetic particles leads to an increase in the shear modulus of the MREs with the tilt chain-like structure. The test results can provide the fundamental characteristics of MREs for the application design.